Immune Tolerance Induction Using Cell-Based Strategies in Liver Transplantation: Clinical Perspectives - Wang, Pusen; Jiang, Zhongyi; Wang, Chunguang; Liu, Xueni; Li, Hao; Xu, Dingyin; Zhong, Lin (Frontiers in Immunology, 2020)
Liver transplantation (LT) has become the best chance and a routine practice for patients with end-stage liver disease and small hepatocellular carcinoma. However, life-long immunosuppressive regimens could lead to many post-LT complications, including cancer recurrence, infections, dysmetabolic syndrome, and renal injury. Impeccable management of immunosuppressive regimens is indispensable to ensure the best long-term prognosis for LT recipients. This is challenging for these patients, who probably have a post-LT graft survival of more than 10 or even 20 years. Approximately 20% of patients after LT could develop spontaneous operational tolerance. They could maintain normal graft function and histology without any immunosuppressive regimens. Operational tolerance after transplantation has been an attractive and ultimate goal in transplant immunology. The liver, as an immunoregulatory organ, generates an immune hyporesponsive microenvironment under physiological conditions. In this regard, LT recipients may be ideal candidates for studies focusing on operative tolerance. Cell-based strategies are one of the most promising methods for immune tolerance induction, including chimerism induced by hematopoietic stem cells and adoptive transfer of regulatory T cells, regulatory dendritic cells, regulatory macrophages, regulatory B cells, and mesenchymal stromal cells. The safety and the efficacy of many cell products have been evaluated by prospective clinical trials. In this review, we will summarize the latest perspectives on the clinical application of cell-based strategies in LT and will address a number of concerns and future directions regarding these cell products.